On Certain Indefinite Elliptic Integrals (Global Journal of Science Frontier Research, 2013)
In this paper we have developed some formulae related to indefinite integrals in association with Hypergeometric functions.
Keywords: pochhammer symbol; gaussian hypergeometric function; complete elliptic integrals; kampE9; de fE9; riet double hypergeometric function and srivastava2019; s